THE USE OF SOCIALLY SIGNIFICANT CONCEPTS BY NATIVE SPEAKERS OF THE TURCOMAN LANGUAGE (EXPERIMENTAL STUDY) - Shustova, Svetlana; Komarova, Yulia; Karamova, Aigul; Chernousova, Anastasiya; Menshakova, Nadezhda (Revista Inclusiones, 2020)
The article analyzes a fragment of the image of the world in the language consciousness of bilingual Turkmen living in Turkmenistan and speaking fluent Turcoman and Russian. The authors of the article performed a free associative experiment. The stimulus words for the experiment are Motherland, Russia, Migrant, Home, and Family. The choice of the stimulus words is explained by the fact that these concepts actualize the specifics of the mental code and are important cultural constants. The relevance of the research is due to the fact that it allows us to obtain data demonstrating the personal experience of an individual on the one hand, and the language social experience on the other. The associative experiment allows to model the structural and operational parameters of the meaning of a ‘living’ word. The structural method is based on the analysis of semantic connections between the stimulus word and associative reactions.